Evaluation of complete blood count parameters in cardiovascular diseases: An early indicator of prognosis? - Haybar, Habib; Pezeshki, Seyed Mohammad Sadegh; Saki, Najmaldin (Experimental and molecular pathology, 2019)
Studies have been conducted to evaluate the correlation between complete blood count (CBC) indices and cardiovascular diseases (CVDs). Considering the dispersion of these studies as well as reports on prognostic value of CBC parameters in CVDs, we have summarized these findings as a review article for the first time. Relevant English language literature was searched and retrieved from Google Scholar search engine and PubMed database (1996–2018). We used “Complete blood count”, “Cardiovascular disease”, “Red cell distribution width”, and “Mean platelet volume” as keywords. Numerous studies indicated that red cell distribution width (RDW) is an independent prognostic biomarker in relation to CVD diseases. MPV is another considerable prognostic biomarker for CVDs. Elevations of inflammatory markers such as neutrophil to lymphocyte ratio (NLR) in CVD patients (especially in myocardial infarction and heart failure) can be considered as a factor of poor prognosis. RDW can be used as a valuable independent biomarker to investigate the prognosis of patients with heart failure (HF), atherosclerosis, myocardial infarction (MI), and other CVDs. Rapid and stable increase in MPV makes it a reliable prognostic/diagnostic parameter in CVDs such as MI and unstable angina. Among different inflammatory markers the evaluation of total white blood cell count, NLR, monocyte to high-density lipoprotein ratio (MHR) and platelet to lymphocyte ratio (PLR) may have a high value in predicting the prognosis of different CVDs including MI, HF and atherosclerosis in patients. •CBC is a readily available and inexpensive routine test capable of determining prognosis of CVDs.•Increased RDW is associated with poor prognosis of CVDs.•MPV is a risk factor of CVDs and is associated with prognosis of CVDs.•Inflammatory markers such as NLR can predict unfavorable events of CVDs in patients.